ChemInform Abstract: A Chemoselective α‐Aminoxylation of Aryl Ketones: A Cross Dehydrogenative Coupling Reaction Catalyzed by Bu4NI. Issue 16 (March 2016) - Siddaraju, Yogesh; Prabhu, Kandikere Ramaiah
Abstract: Diethyl ketone, acetophenone as well as benzoylacetone do not yield the corresponding products.